Association of Hypotension During Thrombectomy and Outcomes Differs With the Posterior Communicating Artery Patency. Issue 9 (17th June 2021) - Maïer, Benjamin; Robichon, Erwan; Bourcier, Romain; Dargazanli, Cyril; Labreuche, Julien; Thion, Laurie-Anne; Leguen, Morgan; Riem, Romuald; Desilles, Jean-Philippe; Boulouis, Grégoire; Delvoye, François; Hebert, Solène; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Hypotension during endovascular therapy for acute ischemic stroke is associated with worse functional outcomes (FO). Given its important role in intracranial hemodynamics, we investigated whether hypotension during endovascular therapy had the same effect on FO according to the posterior communicating artery (PComA) patency. Methods: We performed a post hoc analysis of the ASTER trial (Contact Aspiration Versus Stent Retriever for Successful Revascularization). Patients were included if they had middle cerebral artery occlusions. Primary outcome was favorable FO, defined by a modified Rankin Scale scores between 0 and 2 at 3 months. Results: One hundred forty-eight patients with middle cerebral artery occlusion were included. In patients with no PComA, an increase in minimum mean arterial pressure was positively associated with favorable FO (odds ratio per 10 mm Hg increase, 1.59 [95%CI, 1.11–2.25]; P =0.010), whereas no association was found in patients with a PComA (odds ratio, 0.77 [95% CI, 0.54–1.08]; P =0.12). Patients with no PComA and longer cumulative time with mean arterial pressure <90 mm Hg or systolic blood pressure <140 mm Hg had significantly lower rates of favorable FO, with an odds ratio per 10-minute increase of 0.75 (95% CI, 0.59–0.94; P =0.010) and 0.74 (95% CI, 0.60–0.91; P =0.003), but not in patients with a PComA. Conclusions: Hypotension during endovascular therapy for middle cerebral artery occlusion is consistently associated with worse FO in patients with no PComA but not in those with a PComA. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02523261.